Evaluating immunochromatographic test kits for diagnosis of acute human leptospirosis: A systematic review - Benjie M. Clemente; Maria Ruth Pineda-Cortel; Oliver Villaflores (Heliyon, 2022)
Background: Leptospirosis, a common zoonotic infection in developing countries, usually progresses to severe conditions and poor outcomes when not detected early. Microscopic agglutination test (MAT) and culture are available but are not accessible in all areas and are usually confined to specialized laboratories. There are several available immunochromatographic test kits (ICT) that offer ease of use, access, and affordability, but diagnostic accuracy is not yet well established. In this paper, we aim to review published literature on the use of ICTs for the detection of leptospirosis and evaluate their diagnostic efficiency. Materials and methods: We systematically searched multiple databases (PubMed, Cochrane Library, and Google Scholar), including gray literature sources for published research articles as of April 13, 2022, on the diagnosis of acute leptospirosis using ICT. We assessed the methodological quality of each article using the revised QUADAS-2. Results: From a total of 41 articles, 30 (73.2%) were identified as potentially relevant after reviewing the title and abstract and eliminating duplicate articles; then, 22 (53.7%) articles were included after scrutinizing and applying the inclusion/exclusion criteria to the full text. Almost all test kits detect IgM antibodies against the Leptospira species except for one which used IgG as a marker for diagnosis of acute leptospirosis. A wide range of sensitivity (15.8%–100.0%) and specificity (37.3%–100.0%) were recorded. Lipopolysaccharide (LPS)-specific Immunochromatographic Lateral Flow Assay presented the highest sensitivity (∼93–100%) and specificity (∼99.19–100%). Conclusion: Rapid diagnosis of acute leptospirosis is highly warranted; however, available test kits present a wide range of diagnostic accuracy. We found that LPS-specific ICT kit has the highest diagnostic efficiency; however, our analysis was limited by the included studies’ heterogeneity in design and reporting; thus, we recommend standardization in the conduct and reporting of diagnostic accuracy of test kits as it is vital to evaluate the reliability of the test kit.